2007
DOI: 10.1248/jhs.53.600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spherosomes on Degradation of Pretilachlor and Esprocarb in Soil

Abstract: The fate of pretilachlor and esprocarb in soil with or without spherosomes was investigated for 71 days. The estimated half-lives of pretilachlor in nonsterile soil with and without spherosomes were calculated to be 35.6 and 54.3 days, respectively, while those of esprocarb in nonsterile soil with and without spherosomes were 35.5 and 44.8 days, respectively. The degradation of these pesticides appeared to be essentially due to the biological activity of the soil. Spherosomes should enhance the rate of pretila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Most of the available literature has been confined to laboratory dissipation studies (Ismail and Handah 1999;Fajardo et al 2000a;Murata et al 2004;Adachi et al 2007), and a few have reported the dissipation of pretilachlor under field conditions of Japan (Fajardo et al 2000b) and Italy (Vidotto et al 2004). In India, limited research has been conducted under coastal ecosystem (Dharumarajan et al 2011) and alpine climate (Sharma et al 2013) whereas there are literature gaps about pretilachlor behaviour in subtropical humid agroclimatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the available literature has been confined to laboratory dissipation studies (Ismail and Handah 1999;Fajardo et al 2000a;Murata et al 2004;Adachi et al 2007), and a few have reported the dissipation of pretilachlor under field conditions of Japan (Fajardo et al 2000b) and Italy (Vidotto et al 2004). In India, limited research has been conducted under coastal ecosystem (Dharumarajan et al 2011) and alpine climate (Sharma et al 2013) whereas there are literature gaps about pretilachlor behaviour in subtropical humid agroclimatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the adsorption properties of spherosomes. [12][13][14] On the basis of the present data, it seems more likely that spherosomes might have a role as adsorbent materials for removal of imidacloprid in soil. Thus, spherosomes could efficiently reduce the uptake of imidacloprid in cucumbers by about 1/5.…”
Section: Recovery Studiesmentioning
confidence: 60%
“…The large herbicidal persistence in soil directly influences the soil microorganisms, which in turn affects the plant growth (Raipuria & Parveen, 2016). A study on 14 C-labeled pretilachlor in sterilized and non-sterilized soils showed that microorganisms enhanced the degradation of pretilachlor (Kotoula-Syka et al, 1997) (Adachi et al, 2007). On the other hand, in sterile soil, pretilachlor amount remained almost unvaried.…”
Section: Biodegradationmentioning
confidence: 99%